Personality and Coping in Peruvian volunteers for poverty alleviation - Gastelumendi Gonçalves, Camila (2013)
This study explores the relationship between coping styles and strategies, and personality styles in a sample of 41 young volunteers of an institution that alleviates poverty in Lima. Peruvian adaptations of COPE and MIPS scales were administered. The results show that volunteers have higher scores on adaptive coping strategies. High scores in some particular personality styles were reported, which allowed to establish a personality profile of this group. According with theoretical framework, most coping strategies correlated with most personality styles, revealing four particular tendencies in these volunteers: they wish to have contact with other people, they usually see positive aspects of situations, they look forward for challenges, and they developed adaptive coping strategies.